Towards an Integrated Approach for Place Brand Management - Erik Braun; Sebastian Zenker (European Regional Science Association (ERSA), 2010)
The number of cities claiming to make use of branding has been growing considerably in the last decade. Competition is one of the key drivers for cities to establish their place as a brand and promoting that place to visitors, investors, companies and residents. Unfortunately, place marketers often believe that the place brand is a controllable and fully manageable communication tool. Yet a brand is by definition a network of associations in consumers' minds and is therefore based on the perceptions of the different target groups, making branding a multi-faceted subject. Furthermore, the perception of a place (brand) can differ significantly given the various target groups' diverse perspectives and interests. Hence, place branding theory as well as practice should focus more on the place brand perception of its different target audiences and develop strategies for how places can build an advantageous place-brand architecture. Combining insights from a literature review of place-related academe and marketing academe, this paper outlines an integrated approach to place brand management called the Place Brand Centre. After reviewing the literature on place branding, brand architecture and customer-focused marketing, the paper contends that a target group-specific sub-branding-strategy is central for effective place brand management of cities. Gaps for future research and practical implications for place brand management are discussed.
Keywords: 330; Place Branding; Place Brand Management; Place Marketing; Place Management; Urban Planning; Customer-orientated Marketing